Down Syndrome: an integrative literature review (2005-2020) (Research, Society and Development, 2021)
The person with Down Syndrome (DS) presents an alteration in the number of autosomes, physical, motor, cognitive and linguistic particularities, requiring a specific requirement for the subject's abilities to be developed in a reinforced way. Thus, the objectives of this article are to review the literature that they discuss despite the difficulties that they experience or that may interfere with the acquisition and development of language in a person with Down Syndrome. In the methodology, an integrative literature review (IR) was carried out on aspects, trends and advances related to Down Syndrome published in the Brazilian Journal of Special Education in the period between 2005 and 2020. It was found that children with DS present considerable difficulties in the development of language, as well as of the family and teachers in dealing with this subject, thus, it is essential that the family, school and other professionals who accompany the child with Down build a relationship based on collaborative work, so that the various knowledge are considered enabling learning hypotheses regarding language acquisition. Among the identified identified, we highlight: an importance of the family in the construction of dialogues; inclusion of daily reading for the child to increase their vocabulary and understand the syntactic associations of the language; work with textual genres by teachers; enable children with DS to have contact with other children with and without the syndrome, so that they can have contact with different languages ​​through games, games, dances and music; if necessary, make use of alternative communication.